2019
DOI: 10.1021/acsami.9b13945
|View full text |Cite
|
Sign up to set email alerts
|

High Power Density Platinum Group Metal-free Cathodes for Polymer Electrolyte Fuel Cells

Abstract: Low cost and high-performing platinum group metal-free (PGM-free) cathodes have the potential to transform the economics of polymer electrolyte fuel cell (PEFC) commercialization. Significant advancements have been made recently in terms of PGM-free catalyst activity and stability. However, before PGM-free catalysts become viable in PEFCs, several technical challenges must be addressed including cathode's fabrication, ionomer integration, and transport losses. Here, we present an integrated optimization of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 28 publications
(57 reference statements)
0
88
0
Order By: Relevance
“…It contains no large-scale agglomerates, cracks, or other common large-scale heterogeneities often found with M-N-C cathodes due to the large carbon aggregates. [25,26] Instead, the structure is consistent with the diameter of the fibers. The macroscale void distribution was quantitatively evaluated using the PoreSpy toolkit.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…It contains no large-scale agglomerates, cracks, or other common large-scale heterogeneities often found with M-N-C cathodes due to the large carbon aggregates. [25,26] Instead, the structure is consistent with the diameter of the fibers. The macroscale void distribution was quantitatively evaluated using the PoreSpy toolkit.…”
mentioning
confidence: 77%
“…Our prior work has shown that 3D electrode structures (e.g., pore size, pore distribution, and catalyst geometry) and ionomer distribution strongly affected the PGM‐free cathodes in MEAs. [ 25,26 ] We further evaluated these macroscopic properties for the promising Co–N–PCNFs cathode by using nano‐CT imaging (with a resolution of about 50 nm). As developed by Komini Babu et al., [ 26 ] the nano‐CT allows us to characterize the overall ionomer distribution by using the Cs + signal in absorption contrast and the pore/solid morphology through Zernike phase contrast.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Lister's group 83 systematically investigated the effect of catalyst particle size on this interaction. Fe-N-C catalysts with various particle sizes were used to prepare MEAs.…”
Section: Effect Of Catalyst Morphologymentioning
confidence: 99%
“…a) Nano-CT images of ionomer distribution in CCLs with various catalyst particle sizes; (b) schematic illustration of catalyst aggregates; (c) EIS plots for CCL with various catalyst particle sizes; (d, e) polarization curves of MEAs prepared with catalysts in various particle sizes; (f) polarization curve of MEA fabricated with the catalyst in 100 nm, measured in the H2-O2 fuel cell.Reproduced with permission83 . Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%